(untitled) (Journal of Enam Medical College, 2012)
Proper selection of donors blood group is essential to prevent transfusion hazards. It is known that ABO antigen is fully developed at birth but the newborn baby does not produce ABO antibodies until 3 to 6 months of age. The ABO antibodies present in the serum of newborn babies are derived from mothers blood due to placental transfer. So the blood group of the newborn baby is done by ABO antigen grouping (forward grouping) only, antibody grouping (reverse grouping) is not required. In case of transfusion of blood in newborn under 4 months of age, cross-matching of donors blood is done with the mothers blood if it is available. We know, recipients same group of blood is always preferable in case of transfusion in adults or older children. But selection of blood for transfusion in the infants under 4 months of age depends on the mothers blood group as well. If the mothers blood group differs from the infants blood group, the infants same group of blood may not be selected for transfusion. For example, if the mothers blood group is O and the newborn blood group is A or B, infants same group A or B group blood could not be transfused, because the anti-A & anti-B antibodies can be derived in the infants serum from mothers blood which may react with the A or B antigen of the donors blood. In this case O group packed RBCs should be selected for transfusion. O group whole blood may contain IgG anti-A and anti-B antibodies in the plasma which can react with the A or B antigen of the infants blood. So to avoid anti-A & anti-B antibodies in O group, plasma should be discarded and the packed RBCs should be transfused. In case of Rh-negative mother with Rh positive baby, Rh antibody may develop in mothers blood and Rh antibody may enter into babys circulation, in this case the infant should be transfused with Rh-negative blood to avoid Rh antigen & antibody reaction. So for the selection of blood for transfusion in newborn baby up to the age of 4 months mothers blood group is important to select the appropriate blood. DOI: http://dx.doi.org/10.3329/jemc.v1i1.11138 J Enam Med Col 2011; 1(1): 36-40